Opinion of dentists and gynecologists on the link between oral health and preterm low birth weight: "Preconception care - treat beyond the box" - Aruna Ganganna; G Devishree (Wolters Kluwer Medknow Publications, 2017)
Background: Periodontal diseases are known to set an inflammatory response at the systemic level which can adversely affect the pregnancy outcomes, and many patients are unaware of this association. Health-care providers play a vital role in educating patients toward maintaining good oral health; hence, our study was planned to evaluate the knowledge, attitude, and practices of dentists' and gynecologists' concerning this link. In addition, referral to the dentists' during the preconception period was also emphasized. Materials and Methods: This was a cross-sectional questionnaire survey conducted among dentists and gynecologists' in the city of Mysore. The participants were divided into two groups and were asked specific questions about the association between oral health and preterm low birth weight (PTLB). Group I constituted the dentists possessing both graduate and postgraduate degree and Group II were the gynecologists'. Results: Seventy-nine percent of the total participants agreed about the link between periodontal health and PTLB. Dentists were more aware of the periodontal changes during pregnancy and stressed on frequent dental checkup during pregnancy. Preconception care was a neglected part of the protocol by the gynecologists', and only 12% of them referred patients to a dentist in the preconception period. Factors significantly associated with knowledge in logistic regression analyses were older age, dentists and the years of experience (>5 years). Conclusion: Knowledge about oral health is important, to maintain good general health; hence, health workers should not miss opportunities to contribute to this health promotion. An integrated work by the dentists and gynecologists may reduce the adverse pregnancy outcomes associated with periodontal diseases.